STUDENTS’ DIFFICULTIES IN LEARNING PRONUNCIATION: A CASE STUDY OF SMP ISLAM TERPADU DHUAFA MERANGIN STUDENTS IN LEARNING ENGLISH - Diyan Andriani (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2021)
This study reveals about students’ difficulties in English pronunciation experienced by learners whose first language is Indonesia language. The subjects of this study were the seventh grade of students at SMP Islam Terpadu Dhuafa Merangin especially class B. They were males.  The instruments of this study were task, interview and recording. In analyzing the data, the researcher used descriptively and statistically. The findings of this study showed that the students had problems in pronunciation because of their had low motivation, exposure and their attitude in learning English pronunciation. It could be seen from the result of the task when the researcher asked them to pronunce the English words and the result of interview.